Conceptualizing age-appropriate care for teenagers and young adults with cancer: a qualitative mixed-methods study - Lea S; Taylor RM; Martins A; Fern LA; Whelan JS; Gibson F (Dove Medical Press, 2018)
Sarah Lea,1 Rachel M Taylor,1 Ana Martins,1 Lorna A Fern,1 Jeremy S Whelan,1 Faith Gibson2,3 1Cancer Division, University College London Hospitals NHS Foundation Trust, London, UK; 2School of Health Sciences, University of Surrey, Guildford, UK; 3Centre for Outcomes and Experience Research in Children’s Health, Illness and Disability, Great Ormond Street Hospital for Children NHS Foundation Trust, London, UK Purpose: Teenage and young adult cancer care in England is centralized around 13 principal treatment centers, alongside linked “designated” hospitals, following recommendations that this population should have access to age-appropriate care. The term age-appropriate care has not yet been defined; it is however the explicit term used when communicating the nature of specialist care. The aim of this study was to develop an evidence-based, contextually relevant and operational model defining age-appropriate care for teenagers and young adults with cancer.Materials and methods: A mixed-methods study was conducted comprising 1) semi-structured interview data from young people with cancer and health care professionals involved in their care; 2) an integrative literature review to identify the current understanding and use of the term age-appropriate care; 3) synthesis of both sets of data to form a conceptual model of age-appropriate care. A combination of qualitative content, thematic and framework analysis techniques was used to analyze and integrate data.Results: Analysis and synthesis across data sources enabled identification of seven core components of age-appropriate care, which were presented as a conceptual model: best treatment; health care professional knowledge; communication, interactions and relationships; recognizing individuality; empowering young people; promoting normality; and the environment. Subthemes emerged which included healthcare professionals clinical and holistic expertise, and the environment comprising both physical and social elements.Conclusion: The proposed model, necessarily constructed from multiple components, presents an evidence-based comprehensive structure for understanding the nature of age-appropriate care. It will be useful for clinicians, health service managers and researchers who are designing, implementing and evaluating interventions that might contribute to the provision of age-appropriate care. While the individual elements of age-appropriate care can exist independently or in part, age-appropriate care is optimal when all seven elements are present and could be applied to the care of young people with long-term conditions other than cancer. Keywords: age-appropriate care, teenagers, adolescents, young adults, young people, cancer, health care delivery, BRIGHTLIGHT